Sound Investment. - Beasley, Sandra (American Scholar)
This article reports on a project to preserve broadcast tapes of concerts of the Detroit Symphony Orchestra in 2008. The project will be financed through a grant from Save America's Treasures. The grant will be administered by the U.S. National Endowment for the Arts. Detroit Symphony archivist Cynthia Korolov estimates that the grant will finance to make digitized versions of the recordings to be stored on computer servers and compact discs. The recordings include concerts with such guest artists as Enrico Caruso, Igor Stravinsky and Richard Strauss.